EXPRESSION OF CONCERN: Analysis of the implementation of teletraining and teleIEC in healthcare services: Case study - Saavedra, Sarita; Pinedo, Lloy; Peña, Tamara (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: https://doi.org/10.4108/eetpht.11.12771
Keywords: public health; telehealth; telemedicine; information technology; COVID-19